Device to Assist the Visually Impaired in Reading Printed or Scanned Documents - Coutinho, Luis Rodolfo Rebouças; Girão, Anaxágoras Maia; Frota, João Batista Bezerra; Silva Jr., Elias Teodoro (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Individuals with visual impairment have their ability to access information limited by the lack of mass literature in Braille. This paper presents an embedded application to aid the visually impaired that allows reading and writing printed and/or digitized documents. The solution, designated PORTÁCTIL, is a device composed of five modules: (1) electromechanical Braille cells, (2) hand motion sensor, (3) processing unit, (4) wireless communication and (5) power supply. The text, locally stored or received by wireless communication, is translated to Braille and displayed following the movement of the hand of the reader. Thus, reading occurs in the same way as in books written in Braille. The device is powered by rechargeable batteries and is capable of receiving texts from smartphones and tablets through Bluetooth. Some prototypes were built and tested by several visually impaired users. The adaptation was very good as well as the acceptance. Properties such as weight / volume, energy consumption and performance were evaluated and are given in the full text.